Maximum likelihood estimation of between and within variations in energy and protein intakes from infancy to adolescence for the Philippines - Bhargava, Alok; Bouis, Howarth E. (Wiley, 1992)
The assesment of subjects' ‘usual’ intake of nutrients is important in assessing relationships between diet and disease and in identifying malnourished sub‐groups of the populations. Estimation of the variation in intakes within subjects over time (‘within variation’) has importance in epidemiologic research; estimation of the between subject variation in the sample has use in defining the recommended dietary allowances that take into account the inter‐individual differences. This paper estimates the between and within variances in the energy and protein intakes of 1189 Filipino children, based on 4 rounds of 24‐hour recall data within a dynamic framework by means of maximum likelihood. The main findings are that the proportion of variation due to the within variance is higher for childern from poorer households. Also, from the estimates of dynamic regression models for nutrient intakes of children and adults, it appears that school programmes that provide subsidized foods with good sources of protein to the poorest among school attendees will be cost effective.